Literation Culture Living at MI Qurrota A'yun - Hermansyah, Hermansyah; Ihlas, Ihlas; Supriyanto, Supriyanto; Rohman, Nur (Al-Adzka: Jurnal Ilmiah Pendidikan Guru Madrasah Ibtidaiyah, 2022)
This research is intended to find out how the model and implementation of literacy culture and its impact on students' willingness to read in Madrasah Ibtidaiyah. The type of research used in this study is descriptive with data collection techniques namely, observation, in-depth interviews and documentation. The data analysis process uses the Miles and Huberman model, namely data reduction, data analysis and drawing conclusions. The research findings show that: 1) The literacy culture model at MI Qurrota A'yun is carried out in three stages, namely through introduction, development and learning; 2) Implementation of cultural literacy is applied inside and outside the classroom with methods of inquiry, questioning, reading, presenting and debriefing and collaboration; 3) The influence of literacy culture on students' interest in reading is effective. This activity shows that the desire to read already exists, students just need to be equipped and facilitated in order to produce students who are truly educated in their literacy aspects.